Pengaruh Pertumbuhan Perusahaan, Debt Default, Ukuran KAP dan Audit Tenure terhadap Opini Audit Going Concern: (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar pada Bursa Efek Indonesia Periode 2019 - 2023) - Elisa Tiurma Gratia; Anissa Amalia Mulya (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to test and analyze the effect of Company Growth, Debt default, KAP Size, and Audit tenure on Going concern Audit Opinions on property dan real estate companies listed on the IDX for the period 2019 - 2023. The sample selection technique used purposive sampling method so that 67 research sample companies were obtained. The analytical tool used in this research is logistic regression analysis using SPSS version 22.0. The results of this study indicate that debt default has a significant positive effect on going concern audit opinion, audit tenure has a significant negative effect on going concern audit opinion, while company growth and KAP size have no effect on going concern audit opinion.